Design and validation of a brief scale to measure effective communication processes in university students. (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2022)
INTRODUCTION: The present research seeks to analyze the psychometric properties of a scale oriented to measure the characteristics of effective communication processes in university students. It was developed from a quantitative methodology using psychometric and statistical techniques for the calculation of the properties of the instrument and its respective adjustment in the context. The sample was collected in a simple random way and consisted of 113 people. Cronbach's alpha was used to estimate reliability, Spearman-Brown's Rho correlation for internal consistency and confirmatory factor analysis with varimax rotation to verify construct validity. As a conclusion it can be stated that the instrument meets the standards described above.
Keywords: Effective communication; channel; medium; process of communication; intensity of communication